Religious Aesthetic Expressions of Theatrical Dato’ Ri Bandang at the Friday Sermons in Gantarang Lalang Bata Village Selayar Regency (Catharsis, 2022)
Currently, many media are used to spread religion, one of which is theater, but it is still very rare to use theater as a medium for spreading religion. It is different in the Gantarang Lalang Bata Village in Selayar Regency, which uses theatrical as a medium in spreading religion through the Friday sermon process. The people of Gantarang Lalang Bata village know this theatrical as Tatrikal Dato' ri Bandang. Therefore, this study used descriptive qualitative research with a research design using a performance studies approach that focused on the aesthetic expression of Dato' ri Bandang's theatrical religion. Dato ri Bandang's theatrical religious expression occurs in three ways: before, during, and after, related to things that are prepared, done, and returned. This research data collection used observation, interviews, and document studies. After analyzing the data, the researchers found that the life of the people in Gantarang Lalangbata Village highly upholds cultural values and ancestral heritage through Friday sermons. They do use not only monotonous audio-visual media but also use more visual media that emphasizes the aesthetic experience of society.